Profiles and Biological Values of Sea Cucumbers: A Mini Review - Masre, Siti Fathiah (Life Sciences, Medicine and Biomedicine, 2018)
Sea cucumbers, blind cylindrical marine invertebrates that live in the ocean intertidal beds have more than thousand species available of varying morphology and colours throughout the world. Sea cucumbers have long been exploited in traditional treatment as a source of natural medicinal compounds. Various nutritional and therapeutic values have been linked to this invertebrate. These creatures have been eaten since ancient times and purported as the most commonly consumed echinoderms. Some important biological activities of sea cucumbers including anti-hypertension, anti-inflammatory, anti-cancer, anti-asthmatic, anti-bacterial and wound healing. Thus, this short review comes with the principal aim to cover the profile, taxonomy, together with nutritional and medicinal properties of sea cucumbers.